Changes In External Respiratory Function, Inflammatory Cytokines, And Brain Natriuretic Peptide Indicators In Chronic Obstructive Pulmonary Disease With Comorbid Ischemic Heart Disease - Nurullayev Bakhtiyor Azimboyevich (The American Journal of Medical Sciences and Pharmaceutical Research, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) and Ischemic Heart Disease (IHD) are leading causes of global morbidity and mortality, frequently coexisting as comorbid conditions. Their interplay creates a complex pathophysiological state that exacerbates the clinical course and worsens prognosis. The simultaneous assessment of pulmonary function, systemic inflammation, and cardiac strain in this comorbid population remains a critical area of investigation. Objective: To study the changes in external respiratory function, the levels of key inflammatory cytokines (IL-6, TNF-α), and brain natriuretic peptide (NT-proBNP) in patients with COPD, particularly when it occurs in comorbidity with IHD. Materials and Methods: A single-center, cross-sectional study was conducted at the Clinics of Tashkent State Medical University. A total of 120 male participants aged 45-70 years were enrolled and divided into three groups: Group 1 (n=40) - patients with COPD alone; Group 2 (n=40) - patients with IHD alone (stable angina, FC II); Group 3 (n=40) - patients with comorbid COPD and IHD. A control group (n=30) of healthy, age-matched individuals was also included. All participants underwent spirometry with bronchodilator testing. Serum levels of IL-6, TNF-α, and NT-proBNP were measured using enzyme-linked immunosorbent assay (ELISA). Results: Patients with comorbid COPD and IHD (Group 3) demonstrated the most pronounced impairments in spirometric parameters (FEV1: 48.2±5.1% pred., FVC: 72.5±6.8% pred., FEV1/FVC: 52.8±4.9%) compared to other groups (p<0.001). These patients also exhibited a significant synergistic increase in inflammatory markers (IL-6: 8.45±1.32 pg/mL; TNF-α: 12.89±2.11 pg/mL) and NT-proBNP levels (485.6±75.4 pg/mL), which were substantially higher than in the groups with isolated diseases (p<0.001). Strong negative correlations were found between FEV1 and IL-6 (r = -0.78, p<0.01), FEV1 and NT-proBNP (r = -0.71, p<0.01), and a strong positive correlation between IL-6 and NT-proBNP (r = 0.82, p<0.01) in the comorbid group. Conclusion: The comorbidity of COPD and IHD leads to a significant mutual aggravation of both conditions, characterized by severe obstructive ventilatory disorders, heightened systemic inflammation, and increased cardiac strain. The strong intercorrelations between these parameters suggest a shared pathophysiological pathway and highlight the need for an integrated diagnostic and therapeutic approach targeting both pulmonary and cardiovascular systems in this high-risk patient population.